Experimental investigation of heat transfer by unsteady natural convection at a vertical flat plate. (June 2019) - Schaub, Michael; Kriegel, Martin; Brandt, Stefan
Highlights: Experimental verification of heat transfer by unsteady natural convection. Quantification of momentary and mean values in the unsteady phase. Investigation of cyclic and step-like changes of boundary conditions. Visualization of unsteady flow structures. Temporary occurrence of Kelvin-Helmholtz vortices. Abstract: The present study considers the influence of unsteady flow structures in natural convection on the heat transfer from a vertical flat plate to air. The mean and momentary intensity of convective heat transfer were determined experimentally for specific variations of the boundary conditions. For cyclic and step-like changing operation modes of a direct-electrically heated, 2 m-high copper plate, laminar, transitional and turbulent flow regimes were considered. Compared to a quasi-stationary approach, mean deviations of up to 22.0% for cyclic variations and up to 30.2% for step-like changes occur during an unsteady phase. The extent of the deviations shows a dependence on the mean Grashof number, as well as further influencing factors. Phenomenological observations of the unsteady convection flow in the form of visualizations show a temporarily increased mixing of the boundary layer, which also deviates distinctly from a quasi-stationary development. In particular, a temporary occurrence of Kelvin-Helmholtz vortices can be observed.